PENGARUH TENAGA KERJA DAN INVESTASI SWASTA SERTA PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN KETIMPANGAN PEMBANGUNAN EKONOMI DI PROVINSI KALIMANTAN TIMUR (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The aims of this study was to determine the effect of labor, private investment and government expenditure to GDP in the province of East Borneo. The effect of labor, government spending and private investment GDP to the inequality of economic development and labor influence private investment and government spending through the GDP of the inequality of economic development. The theory used in this study is the concept of inequality of development among regions, regional economic development theory, labor force, investment and government expenditure theory. This study uses data obtained from the Central Statistics Agency (BPS). The analytical method used in this research is the analysis of the path. From the analysis of the data that I do can be concluded that: (1) Effect of Labor to the GDP amounted to 0.439 means that no significant effect. (2) The effect of private investment to the GDP amounted to -0.146 means that no significant effect. (3) The effect of government spending to the GDP amounted to 0.612 means significant effect to the positive direction of the relationship. (4) the effect of employment to economic development gaps of -2.781 means significant effect to the direction of a negative relationship. (5) the effect of private investment to the economic development gaps of 0.761 means that no significant effect. (6) the effect of government spending on economic development gaps amounting to -0.875 means that no significant effect. (7) the effect of the GDP against the inequality of economic development amounted to 3.298 means significant effect to the positive direction of the relationship. (8) the effect of the GDP of the workforce through economic development gaps of 1.447 with the direction of positive relationships. (9) the effect of private investment through the GDP against the inequality of economic development of -0.481 with a direction of negative (6) the effect of government spending through the GDP against the inequality of economic development amounted to 2.018 with the direction of positive relationships. Keywords: Labor, Private Investment, Government Spending, Gross Domestic Product and Inequality Economic Development.